‘I am the Mau: short stories for young people’ AND the role of fiction in raising human rights awareness with an African perspective - Glasheen, Chemutai Agnes (Curtin University, 2020)
The thesis is a two-fold response to how human rights awareness can be integrated into fiction for secondary schools. The exegesis – framed by the interdisciplinary perspectives of human rights, human rights education, and comparative literature – examines African understandings of human rights against universalist ideas, discusses the relationship between rights and fiction, and analyses five short stories by African writers. My creative work is a collection of ten short stories that interrogate complexity around human rights.